2013
DOI: 10.3109/09638288.2013.845252
|View full text |Cite
|
Sign up to set email alerts
|

Important aspects of participation and participation restrictions in people with a mild intellectual disability

Abstract: The concepts of participation and participation restriction are highly relevant in people with a mild intellectual disability. Self-rated performance might be sufficient to assess participation at a group level. In clinical practices, the relationship between the perceived importance and the actual performance of an activity is essential to assess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 40 publications
0
42
0
2
Order By: Relevance
“…In line with this, we endorse the mentioned philosophical perspective referring to action theory [16]. In this study, the term activities is used simply to denote the whole activity/participation list of things that people may do and the term participation is used to denote actually performed activities with respect to the whole ICF activity/participation list [13,20]. In terms of occupational therapy theory, this usage refers to the more abstract meaning of activity as form in contrast to activity as action [31].…”
Section: Terminology and Underlying Theorymentioning
confidence: 88%
See 1 more Smart Citation
“…In line with this, we endorse the mentioned philosophical perspective referring to action theory [16]. In this study, the term activities is used simply to denote the whole activity/participation list of things that people may do and the term participation is used to denote actually performed activities with respect to the whole ICF activity/participation list [13,20]. In terms of occupational therapy theory, this usage refers to the more abstract meaning of activity as form in contrast to activity as action [31].…”
Section: Terminology and Underlying Theorymentioning
confidence: 88%
“…According to such a philosophical perspective, the tripartite ICF concept of disability does not seem to make sense and might be due to a confusion of the conceptual issue of defining disability and methodological issues related to the need to specify environmental factors with respect to estimations of ability. However, the language of the ICF classification part is somewhat less complicated to use because activities and participation are described in a common list and researchers may focus on the participation aspect [13,14,20]. Participation refers to functioning in the actual environment of the studied persons in contrast to the ICF concept of activities, which refer to a so-called standard environment or assumptions about such an environment [14].…”
mentioning
confidence: 99%
“…Out of all participating adolescents at times 1,142 used the adapted version. The items used in this study are originally used in scales previously developed, used and validated by Stattin and Kerr (2000), Arvidsson et al (2012), Arvidsson (2013), and Kerr and Stattin (2000). Only items used at both time 1 and 2 were included.…”
Section: Instruments and Variables Used In This Studymentioning
confidence: 99%
“…The middle part of that concept -activities -refers to an individual perspective on disability that does not tally with the basic structure of so-called social models, which emphasize that all human actions are situated in a context (Bickenbach et al, 1999;Gustavsson, 2004;Arvidsson, Thyberg, Thyberg & Granlund, 2014). In line with social models that just make a bipartite distinction between a bodily perspective and a social perspective, a precursor of rehabilitation medicine suggested that an individual perspective should be substituted with a social perspective as early as 1912 (Thyberg, Nelson & Thyberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Because activity and participation aspects are classified in a single list, researchers have to pay attention to whether a study takes place in the actual environments of the persons or in a so-called standard environment (WHO, 2001;Arvidsson et al, 2014). In the literature, some studies refer to the ICF tripartite concept without actually using or discussing that structure and some use a somewhat confusing mix of activity and participation concepts.…”
Section: Introductionmentioning
confidence: 99%